Hell and back [large type] - Johnson, Craig, 1961- (Johnson, Craig, 1961- Walt Longmire mystery, 2023)
"What if you woke up lying in the middle of the street in Fort Pratt, Montana, where thirty young Native boys perished in an 1896 boarding school fire? What if every person you encountered in that endless night was dead? What if you were covered in blood and missing a bullet from the gun holstered on your hip? What if there was something out there the Northern Cheyenne refer to as the Éveohtsé-heómėse, the Taker of Souls? What if the only way you know who you are is because your name is printed in the leather sweatband of your cowboy hat, and what if it says your name is Walt Longmire... but you don't remember him?"--